Exhaust energy recovery via catalytic ammonia decomposition to hydrogen for low carbon clean vehicles. (1st February 2021) - Sittichompoo, S.; Nozari, H.; Herreros, J.M.; Serhan, N.; da Silva, J.A.M.; York, A.P.E.; Millington, P.; Tsolakis, A.
Highlights: GDI engine exhaust energy is recovered for on-board NH3 decomposition. Exhaust assisted NH3 decomposition was achieved between 450 °C and 650 °C. NH3 reforming was performed by recovering heat and mixing directly with a part of exhaust gases. Up to 30% improvement in GDI fuel economy and CO2 reduction can be achieved. NH3 production by renewable methods have potential of further reducing CO2 emission. Abstract: The work presented here, demonstrates the on-board exhaust assisted catalytic ammonia (NH3 ) conversion to H2 -N2 using either only exhaust heat (decomposition) or by direct reaction with part of the exhaust gas (reforming). The resultant H2 -N2 gas mixture from the exhaust heat driven thermochemical energy recovery processes contains up to 15% more energy than the reactant NH3 (i.e. for 1 kW of NH3 used in the reaction up to 1.15 kW of H2 is produced). Experimental studies using a rhodium-platinum (Rh-Pt) catalyst and equilibrium calculations in Chemkin using Konnov's 0.6 and Nozari's reduced mechanisms have revealed that complete NH3 conversion occurs at typical gasoline direct injection (GDI) engine exhaust gas temperatures (450 °C–550 °C). By partially replacing gasoline in GDI engine with the resultant (H2 -N2 products, up to 30% reduction in CO2 and fuels consumption can be achieved. Additional benefits can be gained under real engine operation when the benefits of reduced pumping losses, due to intake dilution with H2 -N2 gas, are also considered. Furthermore, the work demonstrates additional benefits in CO2 life cycle for the NH3 use as an energy carrier in transportation and broader combustion power generation systems.